“String of pearls pattern”: report of three cases of non clear-cell acanthoma - Espinosa, Ana Elena Domínguez; Akay, Bengu Nisa; González Ramírez, Roger Adrián (2017)
bstract: The coiled and dotted vessels in a serpiginous arrangement or “string of pearls” is considered a classical vascular pattern associated with clear cell acanthoma. We present three cases of epidermal tumors different from clear cell acanthoma that have the same “string of pearls” vascular pattern. Even though most authors keep considering the “string of pearls” vascular pattern an almost pathognomonic sign of clear-cell acanthoma, the cases presented here suggest that some other epidermal tumors can also show this pattern. Kewbords: Acanthoma; Dermoscopy; Keratosis, seborrheic